TELAAH PEMANFAATAN SOFTWARE AKUNTANSI OLEH USAHA KECIL DAN MENENGAH - Rizky Kurniawan; Pepie Diptyana (The Indonesian Accounting Review, 2011)
It has been noted that high transaction frequency has occurred in Small and Medium Enterprises (SMEs). It is also not easy for them to record the transactions. Previous studies show that utilization of accounting software in SMEs is required for increasing both timely and accurately in financial statement. This study aims to determine the factors that affect SEMs accounting software selection. The data were collected from 45 SMEs in Surabaya and Sidoarjo and then they were tested using logistic regression. It is expected to explore whether price, performance, stability, flexibility, implementing, customization and vendor support in utilization through three groups of time range of decision: nowadays, next five years and next ten years. Despite, this research has failed to support the hypotheses. It was found that modified Microsoft excel is an accounting application which is, in fact, mostly used by SMEs. Accounting software utilization is used for supporting operation function, but not for strategic function. It is assumed, however, that this study has limited respondents. Therefore, further research should get more respondents and propose more robust predictor of decision for f using accounting software.